AGE-DEPENDENT VARIABILITY OF THE DYNAMICS OF LINEAR GROWTH OF SALIX TRIANDRA SHOOTS - Alexey A. Afonin (Siberian Journal of Life Sciences and Agriculture, 2021)
Salix triandra (almond willow) is an established crop, grown for basket-making materials. This species is also used for a wide range of environmental projects. The paper aimed to comparative analysis of the seasonal dynamics of linear growth of shoots in S. triandra clones on stools of different ages. The object of the study is a model inbred-clonal population of S. triandra. Our study analyzed the growing annual shoots on saplings from cuttings. To obtain the material, one- and two-year-old stools of four clones were used. The observations were carried out in the conditions of the vegetative period in the year 2021. The development of shoots occurred in conditions of extremely excessive atmospheric moisture at the beginning of the growing season. The study also assessed the impact of ruderal vegetation.